Kinetic studies of copper-catalyzed homocoupling reactions of arylboronic acids in aqueous micellar media - Hawta K. Abdullah; Mazin A. Othman (Zanco Journal of Pure and Applied Sciences, 2022)
The kinetic studies for copper-catalyzed homocoupling phenylboronic acids (1a-d) have been successfully carried out in an aqueous micellar medium under environmentally benign conditions (water as a solvent, micelle to help solubilize hydrophobic adducts) in this study cetyl trimethyl ammonium bromide (CTAB ) is used as surfactant to produce micelle. Using different copper salts and copper complexes as catalysts under benign to mild conditions at a temperature range (40-65˚C, under air) without the addition of any additives (base, oxidant, and ligands). The reactions were followed using a UV-Vis spectrophotometer and the absorbances were measured at maximum wavelengths for the biphenyl production of each five selected (1a-d). The observed rate constants (kobs) were calculated using a pseudo-first-order equation and unsubstituted 1a was selected for optimization processes. The experimental results showed good to excellent curve fit (R2=0.9967-0.9998) to the pseudo-first-order equation and origin software was used for this purpose. Among all copper catalysts, the observed rate constant (kobs) for cupric acetate (Cu(OAc)2)is much higher than others, (kobs=0.1605 min-1), while CuCl2.2H2O has a minimum observed rate constant, kobs=0.0216min-1. The two copper complexes [Cu(4-mba)2(tmeda)], and [Cu(3-mba)2(H2O)2(tmeda)] require a mild condition (85˚C) which is higher than other copper catalysts when 1a is used as reactant the value of kobs is (0.0176, 0.0343 min-1) respectively, while using p-tolylboronic acid (1b) as reactant the value of kobs is (0.0173, 0.0147 min-1) respectively.